An Insights Association Initiative: Insights to Impact. Issue 69 (26th April 2018) - Chadwick, Simon
Abstract : Research World asked market research associations to tell us more about their initiatives in 2018. Our aim is that you, our readers, have a 1 stop shop in understanding where to go for what initiatives. First in this issue is the Insights Association and their Insights to Impact Initiative.